2019
DOI: 10.1038/s41598-019-42751-4
|View full text |Cite|
|
Sign up to set email alerts
|

Airway surface liquid acidification initiates host defense abnormalities in Cystic Fibrosis

Abstract: Cystic fibrosis (CF) is caused by defective Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) protein. Morbidity is mainly due to early airway infection. We hypothesized that S. aureus clearance during the first hours of infection was impaired in CF human Airway Surface Liquid (ASL) because of a lowered pH. The ASL pH of human bronchial epithelial cell lines and primary respiratory cells from healthy controls (WT) and patients with CF was measured with a pH microelectrode. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 39 publications
8
80
1
Order By: Relevance
“…Investigating colocalization of the GWAS p-values with HNE eQTLs for other genes at the locus indicates no significant eQTLs (ANKRD20A10P, ATP12A, RNF17), or a lack of expression in HNE (RNY1P7, RPL26P34, IRX1P1) (Figure 2a, c). Taken together, while biological studies suggest a role for ATP12A in the lung [17][18][19] and have advocated for ATP12A as an alternative CF therapeutic target [23], our studies in the CF population do not support that common variation in expression of this gene affects lung function outcomes.…”
Section: Colocalization Analysis With Locusfocus Near Atp12acontrasting
confidence: 84%
See 2 more Smart Citations
“…Investigating colocalization of the GWAS p-values with HNE eQTLs for other genes at the locus indicates no significant eQTLs (ANKRD20A10P, ATP12A, RNF17), or a lack of expression in HNE (RNY1P7, RPL26P34, IRX1P1) (Figure 2a, c). Taken together, while biological studies suggest a role for ATP12A in the lung [17][18][19] and have advocated for ATP12A as an alternative CF therapeutic target [23], our studies in the CF population do not support that common variation in expression of this gene affects lung function outcomes.…”
Section: Colocalization Analysis With Locusfocus Near Atp12acontrasting
confidence: 84%
“…Results support strong colocalization for ATP12A in the pancreas as reported [11]. Interestingly, ATP12A has been proposed as a modifier of lung disease severity via its role in pH regulation, which in turn may influence immune response to infections in the CF lung [17][18][19]. Our GWAS on lung disease severity in CF, however, revealed no association at this locus [20].…”
Section: Colocalization Analysis With Locusfocus Near Atp12asupporting
confidence: 75%
See 1 more Smart Citation
“…One possible explanation for reduced activity is that acid sphingomyelinase function is known to be pH dependent (activity increases as pH lowers to an optimum of around 5) (33,34). The pH of the airway surface liquid in CF remains keenly debated; however, there is some evidence to suggest that homeostasis is disordered and that the pH is lowered (3,4,(35)(36)(37)(38). Another potential explanation is that acid ceramidase and acid sphingomyelinase are known to exist in a complex with interconnected functions (19).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an acidified environment is beneficial for bacteria survival. In vivo studies on CF newborn pigs and in vitro data obtained on human airway epithelial cells have demonstrated that bacterial killing is impaired in CF due to more acidic ASL pH ( Pezzulo et al, 2012 ; Simonin et al, 2019 ).…”
Section: Inflammation In Cf Airwaymentioning
confidence: 99%